The future of world oil - Eckbo, Paul Leo. (Cambridge, Massachusetts Ballinger Publishing Company, 1976)
This book attempts to develop a framework to analyse the implications of the likely degree of noncompetitive behavior in the international petroleum market
Originally presented as the author's thesis, Massachusetts Institute of Technology, 1975.
Includes bibliographical references [p. 129-137.] and index.
ijb, 15/01/2019
Loans
Keywords: Petroleum industry and trade; Petroleum products; Trusts, Industrial; World oil